SISTEM PEMBAGIAN WARISAN PADA MASYARAKAT MULTIKULTURAL: STUDI DI DESA TELUK PANJI II KECAMATAN KAMPUNG RAKYAT KABUPATEN LABUHAN BATU SELATAN SUMATERA UTARA - Nisa, Khoirun (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Indonesian state is constituted of various races and cultures which reflect plural societies and create culture, art, and different customs as informal education of the society. Multicultural society is a society that acknowledges plurality as the matter of Indonesian nation. This kind of society can be easily found at Teluk Panji II village characterized as one of transmigration areas. Inter-cultural harmony is also depicted through marital system with different cultural background. For example, multicultural society will contribute to create equal position of different cultures. Multicultural society is relatively new term which is introduced by Canadian State around 1970s. This furthermore produces cultural fusion which bounds the relationship of plural society into multicultural one adhering to different kinship system. In sum, the law of inheritance implemented differs with those applied among families concluded through endogamy marriage.